Preliminary Study: Effects of Social Instability Stress on Depressive Behaviours in Ovariectomised Rats - Al-Rahbi, Badriya; Zakaria, Rahimah; Muthuraju, Sangu; Othman, Zahiruddin; Hassan, Asma (Penerbit USM, 2013)
Background: Depression is one of the common post-menopausal symptoms. In addition to estrogen deiciency, social instability stress may contribute as an additional underlying factor in the development of depressive behaviour in females. Therefore, this study was aimed at examining the inluence of social instability stress on depressive behaviour in ovariectomized rats. Methods: The rats were divided into four groups (n = 5 per group); (i) sham-operated control without stress, (ii) sham-operated control with stress, (iii) ovariectomized without stress, and (iv) ovariectomized with stress. These rats were subjected to social instability stress procedures for 15 days prior to an enforced swimming test. Struggling, immobility, and swimming times were recorded promptly. Results: The results were analysed using the one-way analysis of variance (ANOVA) and a P value of < 0.05 was considered as signiicant. The mean durations of struggling, immobility, and swimming behaviour were signiicantly distinct among the four groups. Ovariectomized rats exhibited a substantial decrease in struggling and swimming behaviour, and an increase in immobility behaviour in comparison with the sham-operated controls (P < 0.05). Ovariectomized rats with stress displayed a supplementary decrease in struggling and swimming behaviour as well as an advanced increase in immobility behaviour, compared to sham-operated controls with or without stress (P < 0.05). Conclusion: In summary, these indings suggest that ovariectomized rats encountered an augmented amount of depressive behaviour following social instability stress.